Trends of the second measles vaccine (MCV2) over time after its launch as part of routine immunization in Nigeria: a brief research report - Sato, Ryoko (Frontiers in Public Health, 2024)
Introduction Nigeria has one of the highest measles burdens and the lowest vaccination coverage in the world. Geographical disparity in the coverage has also been persistent. Between 2019 and 2021, the Nigerian government introduced the second Measles vaccine (MCV2) into routine immunization (RI). This study evaluated the trends of the MCV2 coverage over time across geographical zones. Methods The monthly data on the MCV2 coverage from District Health Information Software (DHIS2) for all the health facilities in Nigeria were aggregated by the geopolitical zone, and the trend of the MCV2 coverage was analyzed over time. Results The MCV2 coverage in each zone was approximately 20% when the MCV2 program was launched. The MCV2 coverage was higher in the northern zones (35–42%) than in the southern zones (22–31%) 1 year after the launch. Similarly, at 2.5 years, the MCV2 coverage ranged from 38 to 46% in northern zones, while in southern zones, it ranged from 23 to 37%. Discussion and conclusion The introduction of MCV2 as part of the RI schedule potentially narrows down the health inequity in Nigeria.